Clinician views and experiences of non‐invasive prenatal genetic screening tests in Australia. (10th May 2022) - McKinn, Shannon; Javid, Nasrin; Newson, Ainsley J.; Freeman, Lucinda; Bonner, Carissa; Shand, Antonia W.; Nassar, Natasha; Bell, Katy J.L.
Abstract : Background: Non‐invasive prenatal screening (NIPS) is being increasingly used by expectant parents. Much provision of this test in Australia is occurring in clinical settings where specialised genetic counselling is unavailable, such as general practice. Potential psychosocial consequences from this kind of prenatal genetic screening remain largely unexplored. Aims: To explore clinicians' experiences with NIPS for aneuploidy, their perspectives of the benefits and harms of NIPS, clinicians' information needs, and their perceptions of the needs of expectant parents. Materials and Methods: Qualitative, semi‐structured interviews with 17 health professionals (clinical geneticists, obstetricians, genetic counsellors and general practitioners) who request and counsel for NIPS in Australian hospital and private practice settings, conducted between June 2019 and February 2020. Results: Five themes were identified relating to clinicians' perceptions and experiences of NIPS in their practice: perceived benefits of NIPS, perceived harms of NIPS (with two subthemes: clinical harms and psychosocial harms), financial and equity‐related concerns, counselling as a protective buffer against perceived harms, and clinicians' unmet education needs. While clinicians view NIPS as a useful and high‐quality screening test, especially for detection of common trisomies, many participants had concerns about how NIPS has been implemented in practice, particularly the quality (and often absence) of pre‐/post‐test counselling and the routinisation of testing for sex chromosome aneuploidies, microdeletion and microduplication syndromes. Conclusion: These findings support the need for targeted clinician training around NIPS, and for a shared decision‐making approach to support expectant parents' autonomous decisions about NIPS.